Аналітичне дослідження виробничого травматизму на м'ясопереробних підприємствах - Євтушенко, Ольга Володимирівна (My University, 2014)
Представлена стаття присвячена дослідженню показників виробничого травматизму на підприємствах м’ясопереробної галузі України. Встановлено, що організаційні (порушення трудової і виробничої дисципліни, невикористання засобів індивідуального захисту, невиконання посадових обов’язків, невиконання інструкцій з охорони праці тощо) та кваліфікаційні (відсутність або неякісне проведення інструктажу, допуск до роботи без навчання та перевірки знань з охорони праці, порушення вимог безпеки під час експлуатації обладнання, устаткування, машин, механізмів) фактори на м’ясопереробних підприємствах харчової промисловості України призводять до 90 % виробничих травм. A present study is focused on analysis of industrial traumatism indications at the factories of meat-processing branch in Ukraine. We have determined that 90 % of factory accidents are happening because of organisational (labor and industrial discipline violations, non-usage of personal protective equipment, unfulfillment of the work duties, non-execution of occupational safety regulations) and qualificational (lack of instructions or their poor quality, giving permission to work without OSH training and testing, violation of safety requirements during exploitation of equipment, machinery, vehicles and mechanisms) issues. An approach is suggested for reasons-and-types analysis of events which caused accidents among the manufacturing personnel. It is based on multivariate regressive analysis and gives the opportunity to consider simultaneous effects of many factors, in comparison to the traditional methods of traumatism analysis, where each reason or type of event is examined separately. Results of such analysis and prognosis no doubt have to become a basis for development of preventive measures to avoid industrial traumatism accidents and create safe working conditions for personnel.
Keywords: виробничий травматизм; нещасний випадок; безпека; праця; industrial traumatism; accident; safety; work; кафедра екології та екоменеджменту